Genome-Wide Identification and Expression Analysis of the REF Genes in 17 Species - Jinkai Fang; Chi Ma; Yu Lin; Junjun Yin; Lijuan Zhu; Zhineng Yuan; Dan Zhang (Current Issues in Molecular Biology)
Natural rubber production currently relies heavily on a single species, Hevea brasiliensis, underscoring the urgent need to identify alternative sources to alleviate the strain on natural rubber production. The rubber elongation factor (REF) and small rubber particle protein (SRPP), both members of the REF/SRPP gene family, are crucial for natural rubber biosynthesis. However, research on the REF gene has predominantly focused on H. brasiliensis and Taraxacum kok-saghyz. We conducted a comprehensive genome-wide identification and characterization of the REF gene, identifying 87 REF protein sequences across 17 plants species. We observed a significant increase in the copy numbers and expression of REF genes in rubber-producing plants. Notably, in H. brasiliensis, T. kok-saghyz, Eucommia ulmoides, Lactuca sativa, and other rubber-yielding species, the number of REF genes has markedly increased. Furthermore, some REF genes in H. brasiliensis form a distinct clade in phylogenetic analyses and exhibit differences in conserved motif arrangements and tertiary protein structures compared to other REF genes. These findings suggest that REF genes in rubber-producing plants may have undergone independent evolution, leading to changes in copy number and structure. These alterations could contribute to the production of natural rubber in these species. The results of this study provide a scientific basis for further research into the mechanisms of rubber production in plants and for identifying potential rubber-producing species.